Ablation behavior of C/C-ZrC and C/SiC-ZrC composites fabricated by a joint process of slurry impregnation and chemical vapor infiltration. Issue 5 (1st April 2018) - Zhou, Haijun; Ni, Dewei; He, Ping; Yang, Jinshan; Hu, Jianbao; Dong, Shaoming
Abstract: C/C-ZrC and C/SiC-ZrC composites were fabricated by a joint process of slurry impregnation and chemical vapor infiltration, in which ZrC matrix was obtained by slurry impregnation process, while C or SiC matrix was introduced by chemical vapor infiltration process. The as fabricated C/C-ZrC and C/SiC-ZrC composites have densities of 1.67 g cm −3 and 1.91 g cm −3 respectively. Tensile strength is 89.4±8.4 MPa and 182.2±14.0 MPa respectively for the as prepared C/C-ZrC and C/SiC-ZrC. Ablation behavior of the C/C-ZrC and C/SiC-ZrC composites under air plasma was studied and compared in detail. Due to different oxidation resistance and heat transfer capacity of the matrix, these two ZrC based composites showed various ablation behavior. The linear erosion rate is 48 µm s −1 and 39 µm s −1 respectively for C/C-ZrC and C/SiC-ZrC composites.